Pengaruh Kontribusi Pajak Restoran, Pajak Hiburan, Pajak Reklame Terhadap Pendapatan Asli Daerah Provinsi DKI Jakarta - Nadya Rahmadini; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine the contribution of restaurant tax, entertainment tax, and advertisement tax toward local original income of DKI Jakarta Province. This study uses a saturated sampling technique, namely the realization of restaurant tax revenues, entertainment taxes, advertisement taxes, and local original income for the DKI Jakarta Province from 2014 to 2019. The results of the study show that partially restaurant taxes, entertainment taxes, and advertisement taxes have no significant effect to local original income. Simultaneously restaurant tax, entertainment tax and advertisement tax have no significant effect on the regional revenue of DKI Jakarta Province in 2014 – 2019.